(untitled) - Philippines; Bureau of Agricultural Research (Quezon city, Philippines, 1990)
This set of books has 11 volumes and the content is devided into 11 modules including Overview and directions of agricultural research; The farming systems approach; Organizing multidisciplinary teams; Feedback mechanisms; Planning on-farm research; Cropping systems research; Crop-livestock systems; Fisheries; Post-production; Pilot production programs; and Data management
Keywords: Agricultural; Research,On-farm